Gathering narratives: Athletes` experiences preparing for the Tokyo summer Olympic Games during a global pandemic - Rogers, M.; Werthner, P. (Journal of Applied Sport Psychology, 2023)
The COVID-19 pandemic, and the Tokyo Olympic Games postponement, has created unprecedented challenges for Olympic level athletes. Given the adversity athletes have faced since the World Health Organization (WHO) declared COVID-19 a global pandemic, the construct of psychological resilience is a useful framework for understanding athlete experiences during this time, and is conceptualized by Fletcher and Sarkar as an individual`s ability to protect against the negative effect of stressors. The purpose of this research was to explore the experiences of Canadian athletes preparing for the Tokyo summer Olympic Games during the COVID-19 global pandemic. Interviews were conducted with 20 Canadian athletes across individual and team sports. The participants spoke of the multiple ways they were taking care of themselves and developing resilience throughout the pandemic, highlighting the complexity involved with managing an adversity. Four narratives illuminate the athletes` experiences: the critical role of context, the essential nature of social support, the importance of being more than an athlete, and the relevance of learning to reflect on one`s life. For these athletes, factors such as Olympic qualification, stage of their career, physical and mental health, and access to resources influenced their experience of the pandemic, demonstrating the importance of both individual and environmental factors when exploring resilience. Importantly, the athletes did not manage this adversity on their own, but received strong support. Therefore, sport psychology consultants can assist an athlete`s development of resilience by providing expertise and taking into account an athlete`s personal context.